2006
DOI: 10.1037/0033-2909.132.4.582
|View full text |Cite
|
Sign up to set email alerts
|

Aging and self-regulated language processing.

Abstract: This paper introduces an adult developmental model of self-regulated language processing (SRLP), in which the allocation policy with which a reader engages text is driven by declines in processing capacity, growth in knowledge-based processes, and age-related shifts in reading goals. Evidence is presented to show that the individual reader's allocation policy is consistent across time and across different types of text, can serve a compensatory function in relation to abilities, and is predictive of subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
170
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 166 publications
(200 citation statements)
references
References 299 publications
(481 reference statements)
26
170
1
3
Order By: Relevance
“…The data reported here suggest that the implementation, through repeated exercise, of attentional engagement can mitigate the characteristic declines in cognitive abilities that typically accompany aging (also see Kramer et al 2004;Stine-Morrow et al 2006). It is worth noting that subregions of the prefrontal cortex (PFC) may play a critical role in the mediation of general cognitive performance through their regulation of attentional control and/ or working memory capacity (Sawaguchi and Goldman-Rakic 1991;Durstewitz et al 2000;Thurley et al 2008;Kolata et al 2010; for review, see Matzel and Kolata 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The data reported here suggest that the implementation, through repeated exercise, of attentional engagement can mitigate the characteristic declines in cognitive abilities that typically accompany aging (also see Kramer et al 2004;Stine-Morrow et al 2006). It is worth noting that subregions of the prefrontal cortex (PFC) may play a critical role in the mediation of general cognitive performance through their regulation of attentional control and/ or working memory capacity (Sawaguchi and Goldman-Rakic 1991;Durstewitz et al 2000;Thurley et al 2008;Kolata et al 2010; for review, see Matzel and Kolata 2010).…”
Section: Discussionmentioning
confidence: 99%
“…That is, although one can speak of relatively general cognitive abilities (such as Horn and Cattell's fluidintelligence construct; Cattell, 1971;Horn, 1989;Horn & Cattell, 1966), cognition in the real world is, in our view, usually influenced by relevant knowledge structures (Bartlett, 1932;Ericsson & Kintsch, 1995;Masunaga & Horn, 2001). For instance, knowledge plays a critical role in activities such as reading comprehension, reasoning about possible actions in social contexts, and learning new information (e.g., Hertzog, Dunlosky, & Robinson, 2008;Stine-Morrow, Miller, & Hertzog, 2006). Almost inevitably, new learning builds on the scaffold of what is already known.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…In other words, knowledge derived from schemas, other domains, or a lifetime of reading experiences may contribute to a greater efficiency with which processing resources are expended during the construction of mental representations of text and may help older adults to maintain levels of situation model processing similar to those of younger adults (Stine-Morrow et al, 2006).…”
Section: Agingmentioning
confidence: 99%
“…Individual differences in how resources are allocated (e.g., Stine-Morrow, Miller, & Hertzog, 2006) in conjunction with age also seem to play a role in situation model construction. A study on spatial updating of objects in a building by younger and older adults demonstrated that older adults who were better comprehenders differentially allocated more time to process sentences that did not mention target object locations than did poorer older comprehenders (Morrow et al, 1997).…”
Section: Situation Models and Working Memorymentioning
confidence: 99%